Effects of Thinking and Language Learning Integrated Model to Better the Academic Reading Skill of English Teachers - Unnanantn Thassanant (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study attempted to develop the academic reading skill of English teacher trainees at the Faculty of Education, Suan Sunandha Rajabhat University. PLADSER Model was implemented and the participants’ opinions were surveyed. Eighty one English teacher trainees were the sampling group. The tools were a syllabus in accordance with the model, learning activities’ worksheets, evaluation criteria on academic reading achievement, and an opinion survey form. The results revealed that the scores of the learning activity 1 and 2 were rated as good at the percentage of 78.22 and 84.66, respectively. However, the score percentage of the learning activity 3 was 73.42 and rated as average. In the learning activity 4 which was research idea presentation after reading, their score results were at the percentage of 76.01 or at the good level. From the opinion survey, 91.36 percent of them considered the information structuring methods for research were applicable. Meanwhile, 12.35 percent of them informed that obedience to detailed research methods caused mental difficulties in actual performance